LITERATURA: uma proposta dialógica para a leitura de gêneros literários - BARBOSA, CLEMIUDA (2020)
This research has as a proposal analyzes the theory of literary genre; as a study object for instrumentalize the pedagogical practices by means of a dialogical methodology of the literary reading. The studies are aimed at encouraging in scholar practices the formation of readers. It is assumed that students spend long years at school, and even so most of them do not acquire a pleasure for reading, then it results in difficulties to read and understand texts of different genres. As a result, some of them get out the school context before completing high school. Based on this principle, the research has a bibliographic character and qualitative nature, because the goal is to contribute to the formation of a society composed of fluent readers. In the context of literature classes, it is believed that reading on literary works contributes to the creation of fundamental meanings for teaching and learning of the students. This study marks out a guiding proposal that leads to this formation. The theoretical background guides to reflections and appointments on bakhtinian dialogism; to elucidate the importance of discursive genres, specifically, the literary ones. The listed discussions consider that school knowledge is responsible to human beings’ training in their relations with society. To this end, the suggestions for methodological directions reading and comprehension practices of literary genres show examples from the João Guimarães Rosa’s tale reading. It is hoped that this research instrumentalize teachers and it serves as a model for classes to be applied, with the purpose to awake the students’ interest by the literature. Considering the Brazilian education reality, the formation of the reader is a challenge that instigates discussions and it also emerges in order to new researches can be performed.